A New In Vivo Model to Study Protective Immunity to Zika Virus Infection in Mice With Intact Type I Interferon Signaling - Nazerai, Loulieta; Schøller, Amalie Skak; Rasmussen, Peter Overbeck Sharma; Buus, Søren; Stryhn, Anette; Christensen, Jan Pravsgaard; Thomsen, Allan Randrup (Frontiers in Immunology, 2018)
The association between recent Zika virus infection and neurological complications, microcephaly in the fetus and Guillain-Barré syndrome in adults, underscores the necessity for a protective vaccine. Rational vaccine development requires an in-depth understanding of the mechanisms which could protect against infection with this virus. However, so far such an analysis has been hampered by the absence of a suitable small animal model. Unlike the situation in humans, Zika virus only replicates effectively in the peripheral organs of mice, if type I IFN signaling is interrupted. As type I IFN also impacts the adaptive immune response, mice with such a defect are not optimal for a comprehensive immunological analysis. In this report we show even in wild type mice i.c. infection with low doses of virus causes marked local virus replication and lethal encephalitis in naïve mice. Furthermore, peripheral infection of wild type mice with low doses of virus induces a significant immune response, which provides long-lasting protection of wild type mice from a fatal outcome of subsequent i.c. challenge. Therefore, combining peripheral priming with later i.c. challenge represents a new approach for studying the adaptive immune response to Zika virus in mice with an intact type I IFN response. In this study we focused on the mechanisms underlying resistance to reinfection. Using a combination of adoptive transfer, antibody-based cell depletion and gene targeting, we show that the key protective factor in type I IFN replete mice is humoral immunity. CD8 T cells are not essential in mice with preformed antibodies, but under conditions where initial antibody levels are low, effector CD8 T cells may play a role as a back-up system. These results have important implications for our understanding of natural immunity to Zika virus infection and for Zika vaccine design.